Exploring Reading Strategies Used by Students Based on Metacognitive Awareness - Nisrina Nisrina (Universitas Ahmad Dahlan, 2023)
The crucial impact of knowing about learners reading strategies to acquire a second language has been widely accepted. Therefore, this paper reports a study investigating university students' awareness of their reading strategies when they read English academic texts. As many as 39 first-year university students took part as the research subject, and they answered a 30-item questionnaire on reading strategies. A four-point Likert Scale questionnaire named SORS (Survey of Reading Strategies) was deployed to collect the data concerning the use of reading strategies. The results indicated that among the three reading strategies, the students tended to use Problem-solving strategies more, followed by the Global Reading Strategies and Support Reading Strategies. Finally, the idea of metacognitive that undergoes before, during, and after reading activities must be equipped by the teachers to fulfil the scarcity in those stages of reading. The findings showed that the mean score of each category varied among the three, and these were discussed considering the reading strategy knowledge base as well as the theoretical and practical implications.